PURCHASE DECISION IN E-COMMERCE: UTILISING CELEBRITY ENDORSEMENT, ADVERTISING APPEAL, AND E-WORD OF MOUTH - Lila Kaban; Metta Angelina (Jurnal Ekonomi, 2022)
Marketing has now adopted technologies in the attempt to increase brand recognition. Due to the COVID-19 pandemic, many companies suffer, yet many even reap more profits, such as e-commerce. The purpose of this research is to figure out whether Celebrity Endorsement, Advertising Appeal, and Electronic Word of Mouth have influence towards customer’s Purchase Decision in one of popular e-commerce in Indonesia called Bukalapak. Through the non-probability sampling type, particularly purposive sampling approach, one hundred respondents are taken as samples. The method in this research is descriptive and causal, and the research type is quantitative research. The data analysis methods used are descriptive statistics, coefficient of correlation, coefficient of determination, linear regression analysis and hypothesis testing through T-Test and F-Test. The T-test shows that Celebrity Endorsement, Advertising Appeal, and Electronic Word of Mouth partially influence the Purchase Decision. The F-Test result shows that all independent variables simultaneously influence Purchase Decision. Out of all, Celebrity Endorsement has the biggest influence on Purchase Decision. The value of coefficient of determination obtained is as much as 80.6% indicating that the customer’s Purchase Decision in Bukalapak is explained by Celebrity Endorsement, Advertising Appeal, and Electronic Word of Mouth. The recommendation given is to ensure the company uses talented and well-known celebrity endorsers, design attractive and unique advertisement, and maintain satisfactory performance to encourage complimentary reviews on its platform.